Vietnam : Joint Staff Assessment of the Poverty Reduction Strategy Paper Progress Report. (IMF Staff Country Reports; Country Report ;, 2004)
This paper reviews the Joint Staff Assessment on the Poverty Reduction Strategy Paper of Vietnam. It analyzes the progress in achieving the Comprehensive Poverty Reduction and Growth Strategy (CPRGS) goals and identifies the challenges. It assesses the macroeconomic performance, structural and social change, progress in reducing poverty, the Vietnam Development Goals, targets of the CPRGS, and the monitoring and evaluation systems. The staff recognizes the country's efforts toward the implementation of the CPRGS, and agree that it provides a credible framework for World Bank and IMF concessional assistance.